2002
DOI: 10.3354/meps242237
|View full text |Cite
|
Sign up to set email alerts
|

Attraction of wild fish to sea-cage fish farms in the south-western Mediterranean Sea: spatial and short-term temporal variability

Abstract: Aggregations of wild fish were counted around 9 floating sea-cage fish farms along a 300 km stretch of the Spanish coastline in the southwestern Mediterranean Sea. Each fish farm cultivated Sparus aurata and Dicentrarchus labrax in 6 to 16 floating sea cages between 10 m and 7.4 km from the coast. During September and October 2001, assemblages of fish were counted on 3 separate days at each of 9 farms. Six 5 min rapid visual counts using SCUBA and covering 11 250 m 3 were performed within each farm complex and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
246
5
5

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 208 publications
(266 citation statements)
references
References 31 publications
10
246
5
5
Order By: Relevance
“…Attractiveness is directly related to availability of food resources, especially remains of feed. These are similar to the findings for marine aquaculture in coastal ecosystems, which also found the effect of attractiveness of these systems (Boyra et al, 2004;Dempster et al, 2002;Håkanson, 2005). The results presented allow the conclusion that remains of feed are used by omnivorous species with large feeding plasticity, which certainly justifies its dominance in sites used for cage aquaculture.…”
Section: Impacts On the Resident Ichthyofauna And Fish Feeding Ecologysupporting
confidence: 79%
See 1 more Smart Citation
“…Attractiveness is directly related to availability of food resources, especially remains of feed. These are similar to the findings for marine aquaculture in coastal ecosystems, which also found the effect of attractiveness of these systems (Boyra et al, 2004;Dempster et al, 2002;Håkanson, 2005). The results presented allow the conclusion that remains of feed are used by omnivorous species with large feeding plasticity, which certainly justifies its dominance in sites used for cage aquaculture.…”
Section: Impacts On the Resident Ichthyofauna And Fish Feeding Ecologysupporting
confidence: 79%
“…These feed losses can cause problems related to eutrophication (Beveridge, 1984) and/or be used as a food resource by local biota (Beveridge, 2004;Håkanson, 2005;Ramos et al, 2008;Vita et al, 2004), resulting in ecological changes around these systems (Beveridge, 2004;Håkanson, 2005;Ramos et al, 2008). Besides these impacts, several authors as Agostinho et al (2007); Beveridge (1984Beveridge ( , 1996Beveridge ( e 2004; Dempster et al (2002) Zanatta et al (2010) discuss the problems of this activity in coastal and inland waters. These authors cite impacts upon water quality and sediment which have implications on the structure of benthic communities, plankton and fish, and furthermore, the inherent scapes of caged fish.…”
mentioning
confidence: 99%
“…Moreover, fish farms attract large aggregations of wild fish in their surroundings (Dempster et al 2002). This concentration of fish increases the fishing pressure around the farms, with commercial and recreational fishing vessels moving around different fish farms along the same coastal area (Arechavala-Lopez et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Akyol and Ertosluk (2010) recorded ABT at Turkish sea bream and sea bass fish farms. Dempster et al (2002) and Fernandez-Jover et al (2008) observed ABT at two sea bream and sea bass cages sited off the Spanish coast. Moreover, fish farmers and fishermen from various sites around the Mediterranean have reported an increase in the number and frequency of occurrence of aggregated ABT in the vicinity of tuna farms.…”
Section: Introductionmentioning
confidence: 99%